Discover new information and insights with the help of IDNLearn.com. Discover detailed answers to your questions with our extensive database of expert knowledge.
Sagot :
The equation of [tex]f(x) = e^{-6x}[/tex] by maclaurin series is [tex]f(x)=\sum_{i=0}^{\infty} \frac{(-6.x)^{i} }{i!}[/tex].
The maclaurin series for f(x) is defined by the following formula:
[tex]f(x) = \sum_{i=0}^{\infty} \frac{f^{(i)} (0)}{i!} .x^{i}[/tex]--------------(1)
Where [tex]f^{i}[/tex] is the i - th derivative of the function
If f(x) = [tex]e^{-6x}[/tex], then the formula of the i - th derivative of the function is:
[tex]f^{i} =(-6)^{i} .e^{-6x}[/tex]----------------------(2)
Then,
[tex]f^{i}(0) = (-6)^{i}[/tex]
Lastly, the equation of the trascendental function by Maclaurin series is: [tex]f(x)=\sum_{i=0}^{\infty} \frac{(-6)^{i}.x^{i} }{i!} \\f(x)=\sum_{i=0}^{\infty} \frac{(-6.x)^{i} }{i!}[/tex]---------------(3)
Hence,
The equation of [tex]f(x) = e^{-6x}[/tex] by maclaurin series is [tex]f(x)=\sum_{i=0}^{\infty} \frac{(-6.x)^{i} }{i!}[/tex].
Find out more information about maclaurin series here
https://brainly.com/question/24179531
#SPJ4
We appreciate your participation in this forum. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. Your questions are important to us at IDNLearn.com. Thanks for stopping by, and come back for more reliable solutions.